Case reportFree-floating thrombus in the inferior caval vein and the right atrium - Ostrowski, Stanisław; Banach, Maciej; Okoński, Piotr; Knopik, Jerzy; Kośmider, Anna; Jaszewski, Ryszard (Archives of Medical Science, 2007)
The diagnosis of free-floating thrombus in the right atrium is still met very rarely and there are no unambiguous recommendations for the way of management with such patients. We present the case of a 65-year-old patient with suspicion of thrombus in the inferior caval vein and the right atrium, who was admitted to the Department of Cardiac Surgery with the symptoms of palpitation, atypical chest pain and easy fatigue. We also discuss the most suitable management with this condition.